Discourse about The News of Ibu Kota Negara (IKN) Indonesia on Instagram: Discourse Analysis on The Posts of @detikcom Account - Fikri, Miftakhul (Universitas Pendidikan Nasional, 2024)
The dissemination of information related to reporting on the Ibu Kota Negara (IKN) has been carried out by several national media accounts one of which is the @detikcom. This research aims to find out how the discourse construction is built by the @detikcom on Instagram regarding the report of IKN. This research is qualitative where the research was carried out analyzing the text in the @detikcom posts regarding the report ofIKN. This research method uses discourse analysis by Teun Van Djik where text analysis in Instagram posts can be analyzed using textual analysis (macro structure, superstructure, and microstructure), social cognition analysis and social context analysis. The results of this research found three posts that had a lot of interactions related to IKN news such as flying cars at IKN and the IKN development process. In textual analysis, discourse construction was found with news titles, sentences and special words that were sensational and could attract public attention. Furthermore, the social cognition analysis found posts from the @detikcom produced by text creators which played a very important role in shaping the discourse of IKN news. Then the social context analysis shows that there are differences between the @detikcom and local media accounts in forming the report of IKN. Finally, this research concludes that the @detikcom has formed a discourse on IKN reporting which can indirectly influence public perception.